Analisis Pengaruh Manajemen Pembiayaan Pendidikan Terhadap Efektivitas Pengelolaan Administrasi Sekolah Menengah Atas - Muthia, Shiffa Nurul; Rusdiana, A.; Syam’iyah, Syam’iyah (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to analyze the effect of educational financing management on the effectiveness of school administrative at SMA Karya Budi Cileunyi, Bandung Regency. Transparent, accountable, and efficient financial governance is considered essential for improving administrative performance in educational institutions.Method – This research employed a quantitative descriptive approach with a population consisting of teachers and education staff. A total of 42 respondents were selected through proportional sampling. Data were collected using questionnaires, supported by documentation and observation. Analysis techniques included validity and reliability tests, normality and homogeneity tests, and hypothesis testing using simple linear regression, t-test, and the coefficient of determination (R²) through SPSS v27.Findings – The analysis revealed that educational financing management (mean = 3.63) and administrative effectiveness (mean = 3.61) were both in the very high category. The t-test result (t = 6.663; p < 0.001) confirmed a significant positive effect of financing management on administrative effectiveness, with an R² value of 0.526, indicating that 52.6% of administrative effectiveness is influenced by financing management. Research Implications – This study contributes to educational management literature by demonstrating how transparent and accountable financing governance enhances school administrative effectiveness. Practically, the findings suggest that schools should strengthen budgeting, accounting, and auditing practices to ensure sustainable and effective administrative management.